Dolarizasyon ve Zimbabve ekonomisi - Chınoda, Tınashe Johnson (My University, 2017)
Enflasyon kontrolünün zayıf, iç taahhüt yeteneğinin eksik ve uluslararası ticaret hacminin fazla olduğu ülkeler; dolarizasyon politikasını izlemeye daha çok eğilimli olmaktadır.

Countries with a history of weak inflation control, a lack of domestic commitment ability and a large volume of international trade are more inclined to adopt dollarization.
Keywords: Dolarizasyon; Ekonomi; Zimbabve; Zimbabve Ekonomisi Dollarization; Zimbabwean Economy